A BRIEF REVIEW OF KHI ON THE FULFILMENT OF FAMILY MAINTENANCE FOR SINGLE MOTHERS BY BIOLOGICAL FATHERS (CASE STUDY OF DAMPANG VILLAGE, GANTARANG SUBDISTRICT, BULUKUMBA REGENCY) - Zikrullah Zikrullah; Ahmad Muhajir; Ismail Kappaja; Andi Muh. Taqiyuddin BN; Ahmad Nuh (JOSH: Journal of Sharia, 2026)
This study aims to discuss a brief review of KHI on the fulfilment of family maintenance for single mothers by biological fathers, using a case study from Dampang Village, Gantarang Subdistrict, Bulukumba Regency. This type of research is qualitative research. The research design is field research. The informants interviewed in this study were several single mothers from Dampang Village, Gantarang Subdistrict, Bulukumba Regency. The results of this study show that: The fulfilment of family expenses for single mothers in Dampang Village, Gantarang Subdistrict, Bulukumba Regency, in the context of the Compilation of Islamic Law (KHI). Based on data obtained from the statements of the three single mothers, all of them stated that after the divorce, their ex-husbands never provided for them and their children. This proves that the reality is not in accordance with the Compilation of Islamic Law (KHI), which states that maintenance is the responsibility of a father towards his biological children, which must be fulfilled even if the marriage bond has been severed. However, in reality, the father's obligation to provide financial support to his children is not fulfilled after divorce, so all financial responsibilities are borne by the mother. Single mothers in Dampang village meet their families' needs by working.